2014
DOI: 10.1128/iai.01483-13
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Extracytoplasmic Function σ Factor σ V Regulates Lysozyme Resistance and Is Necessary for Pathogenesis in the Hamster Model of Infection

Abstract: c Clostridium difficile is a clinically important pathogen and the most common cause of hospital-acquired infectious diarrhea. Expression of the C. difficile gene csfV, which encodes V , an extracytoplasmic function factor, is induced by lysozyme, which damages the peptidoglycan of bacteria. Here we show that V is required for lysozyme resistance in C. difficile. Using microarray analysis, we identified the C. difficile genes whose expression is dependent upon V and is induced by lysozyme. Although the peptido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(126 citation statements)
references
References 51 publications
4
119
3
Order By: Relevance
“…The attenuated growth of the sigV mutant in lysozyme was complemented by expression of sigV from a plasmid, similar to previous studies (see Fig. S1 in the supplemental material) (21). The sigV mutant did not, however, have a growth defect in polymyxin B (Fig.…”
Section: Impact Of Sigd Sigt and Sigv Disruption On Camp Resistancesupporting
confidence: 70%
See 2 more Smart Citations
“…The attenuated growth of the sigV mutant in lysozyme was complemented by expression of sigV from a plasmid, similar to previous studies (see Fig. S1 in the supplemental material) (21). The sigV mutant did not, however, have a growth defect in polymyxin B (Fig.…”
Section: Impact Of Sigd Sigt and Sigv Disruption On Camp Resistancesupporting
confidence: 70%
“…1A), we hypothesized that these mutants would be less fit in vivo. In a previous study, Ho et al demonstrated that a sigV mutant is significantly attenuated in a hamster model of infection (21). However, that study was performed in the JIR8094 strain, which is attenuated for virulence in vivo (46,50).…”
Section: Impact Of Sigd Sigt and Sigv Disruption On Camp Resistancementioning
confidence: 94%
See 1 more Smart Citation
“…The cells were fixed with an acetone-ethanol mixture (at a 1:1 ratio). RNA was isolated from these fixed cells using Trizol reagent (Invitrogen) as previously described (16,20). The resulting RNA was treated with DNase I (Turbo DNA-free kit; Ambion) and purified with RNeasy spin columns (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting RNA was treated with DNase I (Turbo DNA-free kit; Ambion) and purified with RNeasy spin columns (Qiagen). The resulting RNA was processed by the University of Iowa Carver Center for Genomics (Iowa City, IA) with custom C. difficile Roche Nimblegen microarrays (20). RNA from three independent biological replicates grown on different days was used.…”
Section: Methodsmentioning
confidence: 99%